Analisis Model Proporsi Tabarru’ dan Ujrah pada Bisnis Asuransi Jiwa Syariah di Indonesia - Alfin Yudha Utama (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the Tabarru and Ujrah Proportion Model in the Sharia General Insurance Business in Indonesia, specifically what factors influence the determination of the tabarru' and ujrah proportions and their correlation with financial performance. This research uses a qualitative descriptive research method. The subject of this research is the tabarru and ujrah fund proportion model, while the object of the research is the Sharia General Insurance Company where the full Islamic system is registered on the OJK website. Data analysis techniques are ways or methods of processing and processing data into results or information that are valid and easily understood by the general public, so this research uses data reduction techniques, presenting data and drawing conclusions. The results of the research show 1) Contextual constructs include the construct of claims, crackdown activities, and aspects of company finance that influence the company's financial performance. Claims have a significant effect on the proportion of tabarru' funds. 2) Claims are the rights of sharia insurance participants when they experience a disaster, the funds used in paying claims by sharia insurance companies against participants are obtained from the tabarru' fund pool so that when the claim burden increases it requires a large proportion of tabarru' funds, thus encouraging the company to increase the proportion of tabarru' funds. 3). This research also produced a construct correlation model, namely the claim construct, the company's financial aspects, and crackaful activities which influence the proportion of tabarru' and ujrah along with the proportion of tabarru' ujrah which influences the company's financial performance. This research is able to form a model in determining the proportions of tabarru' and ujrah so that this model can be used as a basic model for subsequent researchers.